Answer:
f(x) = (x - 6)/(3/2)
Step-by-step explanation:
1) you would need to turn both fractions so they have a common denominator, that would be 2 2/4 and 3/4
2) then subtract : 2 2/4 - 3/4, and you would subtract numerators and the whole number, but you keep the denominator the same. However, you cannot subtract 2 and 3 in this case, so you need to change 2 2/4 to 1 5/4 (they are still equivalent)
3) 1 5/4 - 3/4 = 1 2/4, which simplified version is 1 1/2
Therefore, the answer is 1 and 1/2
Answer: x= -3.25
Step-by-step explanation:
R=4x+6y 11=4x+6(4) 11=4x+ 24 11-24=4x -13=4x -13/4=x x=-3.25
11=4(-3.25)+ 6(4) 11= -13+24
Answer:
Step-by-step explanation:
![x^{2} \sqrt{x} \sqrt[n]{x} \frac{x}{y} x_{123} \beta \beta \alpha \neq \geq \\ \left \{ {{y=2} \atop {x=2}} \right.](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%5Csqrt%7Bx%7D%20%5Csqrt%5Bn%5D%7Bx%7D%20%5Cfrac%7Bx%7D%7By%7D%20x_%7B123%7D%20%5Cbeta%20%5Cbeta%20%5Calpha%20%5Cneq%20%5Cgeq%20%5C%5C%20%5Cleft%20%5C%7B%20%7B%7By%3D2%7D%20%5Catop%20%7Bx%3D2%7D%7D%20%5Cright.)